Identification of cost data inputs in Life Cycle Cost (LCC) of alternative road pavement types - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin; Bidi, Nor Khalisah; Ahmad Jasmi, Siti Zulaiha (2017)
Life Cycle Cost (LCC) is an economic assessment technique that produces outputs, which can be used to provide cost information to the LCC estimators, clients and researchers in facilitating them to compare the most cost-effective of mutually exclusive alternative road pavement types. LCC estimates total ownership costs of the road pavement which connects the initial capital costs and future costs to produce outputs that can be used to identify potential cost saving and demonstrate value for money procurement. There are different kinds of data to be used as inputs in LCC analysis and the type of data to be used is contingent upon the intended output of the LCC analysis. Past researches reported that the quality, currency and adequacy of data used as inputs in LCC estimation are of paramount importance in effort to produce reliable LCC outputs. The aim of this research is to enhance the quality of data input requirements for a comprehensive and reliable LCC estimation of road pavement types in Malaysian construction industry. The research focuses only on cost data inputs used in estimating LCC. The methodology employed for the research comprised a comprehensive review of related literature and Focus Group Discussion (FGD) with a group of panellists that have experience, skills and knowledge in LCC. The outcomes of the research is a protocol of LCC of data input requirements for two road pavement types (i.e. flexible and rigid pavements) that comprises a flow chart, step by step methodological approach and remarks. The protocol has been developed, evaluated, validated and tested with the FGD panellists to provide appropriate and robust procedures on how the cost data could be made more quality as inputs into the process of estimating LCC and determining the most economic viability of alternative road pavement types.